[(UO2)(C10H8N2O2)2][HPW12O40]: The First Case of a Uranyl Coordination Network Containing a Keggin‐Type Polyoxometalate. Issue 48 (16th November 2020) - Zhang, Chi; Guo, Fengwan; Dai, Yong; Zhang, Yu; Feng, Jing; Wang, Nan; Wang, Juan
Abstract : A uranyl compound [(UO2 )(C10 H8 N2 O2 )2 ][HPW12 O40 ] has been hydrothermally synthesized (150 °C for 72 h) in the presence of typical Keggin‐phosphotungstic acid. This compound exhibits a regular layered structure which is composed of [UO2 ] 2+ and bridging ligand 4, 4'‐bipyridine‐ N ‐dioxide (4, 4'‐BPDO). The nanosized cavities are occupied by Keggin‐anions [HPW12 O40 ] 2– through covalent bonds and hydrogen bonds, in order to hold the charge equilibrium and enhance the stability of the structure. The adsorption properties of this compound have been primarily investigated. The results indicate that the incorporation of Keggin‐anions plays an important role in the fast capture of cationic dye MB + . Compound 1 is the first case of uranyl coordination network decorated by POMs, which evidently provides a feasible strategy for controlling the structural connectivity and functionality of uranyl organic framework. Abstract : A novel 2D uranyl coordination network with regular nanosized cavities has been hydrothermally synthesized. It represents the first uranyl compound decorated by polyoxometalate through a covalent bond. The work affords a feasible strategy for controlling the structural connectivity of uranyl organic framework.